The effect of digital transformation on teacher performance evaluation in Palestinian schools - Masaeed, Madleen Jihad Naji; Shehada, Sanabel Amer Jawdat; Mersal, Mersal Abdullah Sulaiman (Frontiers in Education, 2025)
Digital transformation is defined as a change related to the adoption of digital technology that brings about a radical shift in work methods, aiming to serve beneficiaries more efficiently and quickly. The study aimed to assess the impact of digital transformation within the Ministry of Education, as perceived by Palestinian public school principals. An analytical descriptive curriculum was adopted, and data were collected using a 36-item questionnaire distributed across three dimensions. The study included all principals of public schools in two cities in Palestine. The results indicated that school principals observed a remarkable level of digital transformation within the Ministry of Education. Moreover, a significant correlation was found between digital transformation planning, preparing leaders for digital transformation, and evaluating employee performance. However, no statistically significant relationship was discovered between organizational readiness for digital transformation and employee performance assessment. Researchers recommend that educational institutions develop comprehensive digital transformation programs and provide ongoing training opportunities for teachers.